Global Proteomic Profiling of Piscirickettsia salmonis and Salmon Macrophage-Like Cells during Intracellular Infection - Javiera Ortiz-Severín; Dante Travisany; Alejandro Maass; Verónica Cambiazo; Francisco P. Chávez (Microorganisms, 2020)
Piscirickettsiasalmonis is an intracellular bacterial fish pathogen that causes piscirickettsiosis, a disease with numerous negative impacts in the Chilean salmon farming industry. Although transcriptomic studies of P. salmonis and its host have been performed, dual host–pathogen proteomic approaches during infection are still missing. Considering that gene expression does not always correspond with observed phenotype, and bacteriological culture studies inadequately reflect infection conditions, to improve the existing knowledge for the pathogenicity of P. salmonis, we present here a global proteomic profiling of Salmon salar macrophage-like cell cultures infected with P. salmonis LF-89. The proteomic analyses identified several P. salmonis proteins from two temporally different stages of macrophages infection, some of them related to key functions for bacterial survival in other intracellular pathogens. Metabolic differences were observed in early-stage infection bacteria, compared to late-stage infections. Virulence factors related to membrane, lipopolysaccharide (LPS) and surface component modifications, cell motility, toxins, and secretion systems also varied between the infection stages. Pilus proteins, beta-hemolysin, and the type VI secretion system (T6SS) were characteristic of the early-infection stage, while fimbria, upregulation of 10 toxins or effector proteins, and the Dot/Icm type IV secretion system (T4SS) were representative of the late-infection stage bacteria. Previously described virulence-related genes in P. salmonis plasmids were identified by proteomic assays during infection in SHK-1 cells, accompanied by an increase of mobile-related elements. By comparing the infected and un-infected proteome of SHK-1 cells, we observed changes in cellular and redox homeostasis; innate immune response; microtubules and actin cytoskeleton organization and dynamics; alteration in phagosome components, iron transport, and metabolism; and amino acids, nucleoside, and nucleotide metabolism, together with an overall energy and ATP production alteration. Our global proteomic profiling and the current knowledge of the P. salmonis infection process allowed us to propose a model of the macrophage–P. salmonis interaction.